2015
DOI: 10.1002/pc.23620
|View full text |Cite
|
Sign up to set email alerts
|

Radiation fabrication and characterization of the nanocomposite: Waste polyethylene /ethylene propylene diene/treated nanokaolin

Abstract: In this study, Kaolin modified with vinyltriethoxysilane (SMK) was compounded with the blend, waste polyethylene /ethylene propylene diene monomer (EPDM), 50/50 wt%, by melt intercalation. The effect of SMK loading on the physicomechanical properties of the blend was examined by varying its incorporation (3–15 phr). The composites were irradiated using gamma irradiation within the range 25–200 kGy. Tensile and modulus parameters were investigated at various feed ratios of SMK at variable gamma radiation dose. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…The obtained outcomes are supported by the mechanical and thermal analysis collected data. The appearance of the crystalline phase of filler intercalated in the rubber phase was observed before in EPDM filled with kaolinite [ 18 ] and NBR reinforced with waste ceramic dust. [ 9 ] It is worth noted, that identical XRD pattern was gained for all NBR and SBR nanocomposites, that is, no alteration in crystallinity due to filling with waste nanomarble.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…The obtained outcomes are supported by the mechanical and thermal analysis collected data. The appearance of the crystalline phase of filler intercalated in the rubber phase was observed before in EPDM filled with kaolinite [ 18 ] and NBR reinforced with waste ceramic dust. [ 9 ] It is worth noted, that identical XRD pattern was gained for all NBR and SBR nanocomposites, that is, no alteration in crystallinity due to filling with waste nanomarble.…”
Section: Resultsmentioning
confidence: 73%
“…Furthermore, C–H bond stretching represented in TWM at 2982 cm −1 unlike in its shape and intensity about from appeared in WM itself due to silane treatment. [ 18 ]…”
Section: Resultsmentioning
confidence: 99%
“…Also, the increase in crosslinking density during irradiation is ascribed to inter-polymer chains crosslinking as well as between polymer chains and the silane coupling agent. 24 More important irradiation doses would improve the crosslinking content leading certainly to maintenance and replacement of polymer. 32 The CS values obviously decrease with increasing concentrations of unmodified and modified nanosilica in the NBR matrix at all radiation doses.…”
Section: Resultsmentioning
confidence: 99%
“…9 Also, the increase in crosslinking density during irradiation is ascribed to inter-polymer chains crosslinking as well as between polymer chains and the silane coupling agent. 24 The crosslinking density of NBR/cerium ions composites increases with the increase of the concentration of cerium salts. 25 Abou Zeid 26 was found that values of swelling number of NBR/EPDM blend loaded composites decreased with increasing the degree of loading with the CB filler.…”
Section: Physical Measurementsmentioning
confidence: 97%
“…It was observed that as radiation dose increases up to 100 kGy, the gel content increases at all concentrations. The increase in crosslinking density during irradiation is ascribed to interpolymer chain crosslinking as well as between polymer chains and the silane coupling agent . Thus, the developed crosslinking networks could reduce the solubility of the HDPE matrix in hot benzene and increase the gel content of composites .…”
Section: Resultsmentioning
confidence: 99%